The Role of Biomaterials as Angiogenic Modulators of Spinal Cord Injury: Mimetics of the Spinal Cord, Cell and Angiogenic Factor Delivery Agents - Rocha, Luís A.; Sousa, Rui A.; Learmonth, David. A.; Salgado, António J. (Frontiers in Pharmacology, 2018)
Spinal cord injury (SCI) represents an extremely debilitating condition for which no efficacious treatment is available. One of the main contributors to the inhospitable environment found in SCI is the vascular disruption that happens in the moment of lesion, that leads to a compromise in the blood-spinal cord barrier (BSCB) and to a cascade of events that include infiltration of inflammatory cells, ischemia and intraparenchymal hemorrhage. Due to the unsatisfactory nature of revascularization following SCI, restoring vascular perfusion and the BSCB seems an interesting way of modulating the lesion environment into a regenerative phenotype, with a potential increase in functional recovery. Biomaterials have interesting features to enhance such therapies, and in fact have been applied as angiogenic promoters in other pathologies. Thus, the present mini-review intends to show the importance that biomaterials may have in the development of therapeutic approaches that restore proper vascularization and the BSCB.